Tolerance The Beacon of the Enlightenment - Warman, Caroline (Open Book Classics, 2016)
This anthology, inspired by Voltaire's advice that a text needed to be concise to have real influence, contains firey extracts from forty different authors, from the philosophers everyone's heard of to those whose brilliant writings are less well-known. They are immensely diverse in style and topic, but all have in common their passionate commitment to equality, freedom, and tolerance, and every single one resonates powerfully with the issues our world faces today. The book was first published by the Société française d'étude du dix-huitième siècle (the French Society for Eighteenth-Century Studies) in the wake of the Charlie Hebdo assassinations in January 2015 as a mark of solidarity, and as a response to the wide-spread interest in Enlightenment values. With the support of the British Society for Eighteenth-Century Studies, it has now been translated by 102 French students and tutors from Oxford University.